For n ∈ N , there is a sequence a 1 , a 2 , a 3 , … a n , … such that, a 1 = 2 0 , a 2 = 1 7 and a n = a n − 1 + a n − 2 2 a n − 1 a n − 2 for all n ≥ 3 .
2 0 2 ⋅ 2 0 1 7 2 ⋅ 1 7 ⋅ 1 3 5 5 7 6 ⋅ k = 1 ∑ ∞ 2 0 1 7 k a k 1
What is the remainder when the product above is divided by 1 0 0 0 ?
For more problems like this, try answering this set .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
By Using the Iterative Formula Above, (This Solution Is So Hard and Long. )
a 1 a 2 a 3 a 4 a 5 a 6 ⋮ = 2 0 = 1 7 = 2 0 + 1 7 2 ( 2 0 ) ( 1 7 ) = 3 7 2 3 ⋅ 5 ⋅ 1 7 = 1 7 ( 3 7 3 7 + ( 2 3 ⋅ 5 ) ) 3 7 2 4 ⋅ 5 ⋅ 1 7 2 = 7 7 2 4 ⋅ 5 ⋅ 1 7 = 2 3 ⋅ 5 ⋅ 1 7 ( 3 7 ⋅ 7 7 7 7 + ( 2 ⋅ 3 7 ) ) 7 7 ⋅ 3 7 2 8 ⋅ 5 2 ⋅ 1 7 2 = 7 7 + ( 2 ⋅ 3 7 ) 2 5 ⋅ 5 ⋅ 1 7 = 2 4 ⋅ 5 ⋅ 1 7 ( ( 7 7 + ( 2 ⋅ 3 7 ) ) ⋅ 7 7 7 7 + ( 2 ⋅ 3 7 ) + ( 2 ⋅ 7 7 ) ) 7 7 ⋅ ( 7 7 + ( 2 ⋅ 3 7 ) ) 2 1 0 ⋅ 5 2 ⋅ 1 7 2 = 7 7 + ( 2 ⋅ 3 7 ) + ( 2 ⋅ 7 7 ) 2 6 ⋅ 5 ⋅ 1 7
k = 1 ∑ ∞ 2 0 1 7 k a k 1 = 2 0 1 7 ⋅ 2 0 1 + 2 0 1 7 2 ⋅ 1 7 1 + S
where S = 2 0 1 7 3 ⋅ 2 3 ⋅ 8 5 3 7 + 2 0 1 7 4 ⋅ 2 4 ⋅ 8 5 7 7 + 2 0 1 7 5 ⋅ 2 5 ⋅ 8 5 7 7 + ( 2 ⋅ 3 7 ) + 2 0 1 7 6 ⋅ 2 6 ⋅ 8 5 7 7 + ( 2 ⋅ 3 7 ) + ( 2 ⋅ 7 7 ) + ⋯
Multiplying S by 4 0 3 4 and subtracting the result to S yields:
4 0 3 3 S = 2 0 1 7 2 ⋅ 2 2 ⋅ 8 5 3 7 + 2 0 1 7 3 ⋅ 2 3 ⋅ 8 5 4 0 + 2 ( 4 0 3 4 S ) ⟹ 2 0 1 7 8 1 3 4 5 6 0 S = 4 0 3 4 2 ⋅ 8 5 1 ⋅ 2 0 1 7 7 4 6 4 9 ⟹ S = 4 0 3 4 2 ⋅ 8 5 ⋅ 2 7 1 1 5 2 0 2 4 8 8 3 ⟹ k = 1 ∑ ∞ 2 0 1 7 k a k 1 = 2 0 1 7 1 ( 2 0 1 + 2 0 1 7 ⋅ 1 7 1 + 8 0 6 8 ⋅ 8 5 ⋅ 2 0 ⋅ 1 3 5 5 7 6 2 4 8 8 3 )
⟹ 2 0 2 ⋅ 2 0 1 7 2 ⋅ 1 7 ⋅ 1 3 5 5 7 6 ⋅ 2 0 1 7 1 ( 2 0 1 + 2 0 1 7 ⋅ 1 7 1 + 8 0 6 8 ⋅ 8 5 ⋅ 2 0 ⋅ 1 3 5 5 7 6 2 4 8 8 3 ) = ⎝ ⎛ 2 0 ⋅ 2 0 1 7 ⋅ 1 7 ⋅ 1 3 5 5 7 6 + 2 0 ⋅ 2 0 ⋅ 1 3 5 5 7 6 + 2 4 8 8 3 ⎠ ⎞ m o d 1 0 0 0 ≡ ⎝ ⎛ 2 0 ⋅ 1 7 ⋅ 1 7 ⋅ 5 7 6 + 2 0 ⋅ 2 0 ⋅ 5 7 6 + 8 8 3 ⎠ ⎞ ≡ ⎝ ⎛ 2 8 0 + 4 0 0 + 8 8 3 ⎠ ⎞ ≡ 5 6 3
Problem Loading...
Note Loading...
Set Loading...
a n ⟹ a n 1 2 b n − 1 2 b k = a n − 1 + a n − 2 2 a n − 1 a n − 2 = 2 1 ( a n − 1 1 + a n − 2 1 ) = b n − 2 + b n − 3 = b k − 1 + b k − 2 Let b n − 1 = a n 1 Let k = n − 1
The characteristic equation of the linear recurrence relation of sequence { b n } is given below.
2 r 2 − r − 1 ( 2 r + 1 ) ( r − 1 ) ⟹ r ⟹ b k b 0 c 1 + c 2 − 2 c 1 + c 2 ⟹ c 1 c 2 ⟹ b k = 0 = 0 = − 2 1 , 1 = c 1 ( − 2 1 ) k + c 2 = a 1 1 = 2 0 1 = b 1 = a 2 1 = 1 7 1 = − 1 7 0 1 = 3 4 0 1 9 = 3 4 0 1 9 − 1 7 0 1 ( − 2 1 ) k
Now we have:
k = 1 ∑ ∞ 2 0 1 7 k a k 1 = k = 0 ∑ ∞ 2 0 1 7 k + 1 b k = 2 0 1 7 1 ( 3 4 0 1 9 k = 0 ∑ ∞ 2 0 1 7 k 1 − 1 7 0 1 k = 0 ∑ ∞ ( 4 0 3 4 − 1 ) k ) = 2 0 1 7 1 ( 3 4 0 1 9 ( 1 − 2 0 1 7 1 1 ) − 1 7 0 1 ( 1 + 4 0 3 4 1 1 ) ) = 2 0 1 7 1 ( 3 4 0 1 9 ( 2 0 1 6 2 0 1 7 ) − 1 7 0 1 ( 4 0 3 5 4 0 3 4 ) ) = 3 4 0 ⋅ 2 0 1 6 1 9 − 8 5 ⋅ 4 0 3 5 1 = 9 2 1 9 1 6 8 0 0 2 2 8 6 7
⟹ X = 2 0 2 ⋅ 2 0 1 7 2 ⋅ 1 7 ⋅ 1 3 5 5 7 6 ⋅ k = 1 ∑ ∞ 2 0 1 7 k a k 1 = 2 0 2 ⋅ 2 0 1 7 2 ⋅ 1 7 ⋅ 1 3 5 5 7 6 ⋅ 9 2 1 9 1 6 8 0 0 2 2 8 6 7 = 2 0 1 7 2 ⋅ 2 2 8 6 7 = 1 7 2 ⋅ 8 6 7 (mod 1000) = 2 8 9 ( − 1 3 3 ) (mod 1000) = − 4 3 7 (mod 1000) = 5 6 3 (mod 1000)